Analysis of Production Optimization Strategy to Increase The Capacity of Kamumu Kimpul Chips at UD. Sona Gunungsitoli Idanoi - Yantonius Harefa; Sophia Molinda Kakisina; Jeliswan Berkat Iman Jaya Gea; Martha Surya Dinata Mendrofa (Economics and Business Journal (ECBIS), 2026)
The fast food industry continues to grow as the public's need for practical products, including Kamumu Kimpul chips, increases. However, small business actors such as UD. Sona in Gunungsitoli Idanoi faces obstacles in production due to the use of traditional methods, limited equipment, and lack of optimal management. This condition has an impact on delays in meeting demand, increasing production costs, and declining competitiveness. Therefore, a production optimization strategy is needed to improve product capacity, efficiency, and quality. This study aims to analyze the production optimization strategy implemented by UD. Sona, formulate a capacity building strategy, as well as identify obstacles and solutions that can be done. The results of the research are expected to be practically useful for business actors in production management, as well as make a theoretical contribution to the development of production management science in MSMEs. The research method uses a descriptive qualitative approach. Data was obtained through interviews with owners, employees, and customers, supplemented by observation and documentation. Data analysis is carried out through reduction, presentation, and inductive conclusions, so as to be able to describe the real conditions of the business and develop the right optimization strategy. The results of the study show that UD. Sona has made efforts such as setting up production flows and scheduling planning. However, limited machinery, unstable supply of raw materials, and marketing that has not been maximized are still obstacles. Consumers rate the product as good quality, but its availability has not been consistent. Suggested strategies include the implementation of lean production, improvement of inventory management, and the use of production technology